2020
DOI: 10.11604/pamj.2020.36.134.16652
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of mycobacterium tuberculosis complex by real-time polymerase chain reaction (PCR) in pulmonary and extra-pulmonary samples in Casablanca, Morocco

Abstract: Introduction the laboratory diagnosis of tuberculosis (TB) relies mainly on conventional techniques. However, it either lacks sensitivity or it is time-consuming. This study aims to evaluate the use of real-time polymerase chain reaction (PCR) targeting IS6110 for Mycobacterium tuberculosis (TB) Complex (MTBC) in the routine diagnosis of TB in our laboratory. Methods clinical samples were collected from the laboratory of bacteriology at Ibn Rochd University Hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Other studies reported the assay's sensitivity for detecting rifampicin resistance to be 95% -100%. Specificity was 99%-100% (Fakhreddine et al, 2020;Penn-Nicholson et al, 2021). In the current study, MTB/RIF assay showed 79 samples were RIFsusceptible, and 1 was RIF-resistant.…”
Section: Discussionmentioning
confidence: 50%
“…Other studies reported the assay's sensitivity for detecting rifampicin resistance to be 95% -100%. Specificity was 99%-100% (Fakhreddine et al, 2020;Penn-Nicholson et al, 2021). In the current study, MTB/RIF assay showed 79 samples were RIFsusceptible, and 1 was RIF-resistant.…”
Section: Discussionmentioning
confidence: 50%
“…The colonies were initially identified by Acid-Faststain [14]. We performed a real-time polymerase chain reaction (PCR) of Mycobacterium tuberculosis for Acid-Fast stainpositive colonies [15] and found that the bacteria were not Mycobacterium tuberculosis. Using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS), the colonies were identified as M. fortuitum.…”
Section: Case Presentationmentioning
confidence: 99%